Validation of a Procedure to Determine Distinctive Technological Competences: Application of Petri Nets - Mantulak, Mario José (2022)
Distinctive  technological  competencies  have  become  a  determinant  of  business  competitiveness. Petri nets are very useful when modeling a sequence of actions, their requirements  and  the  restrictions  that  may  arise  in  a  procedure.  The  objective  of  this  work is the modeling and analysis from the workflow networks, derived from the classic Petri nets, of a procedure for the determination of distinctive technological competencies in  manufacturing  companies.  Using  the  Workflow  Petri  net  Designer  software,  a  set  of tasks, conditions and resources required in the procedure have been modeled, and the  feasibility  of  its  execution  has  been  verified.  As  result,  the  design  of  the  stages  and the corresponding requirements in terms of conditions, resources and information flows  that  make  up  the  procedure  were  obtained,  as  well  as  the  verification  of  the  feasibility of applying the tool for the outlined purposes.